2008
DOI: 10.1128/mcb.00808-08
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3β-Mediated Serine Phosphorylation of the Human Glucocorticoid Receptor Redirects Gene Expression Profiles

Abstract: Aberrant glycogen synthase kinase 3␤ (GSK-3␤) activity is associated with the progression of several pathological conditions such as diabetes, Alzheimer's, and cancer. GSK-3␤ regulates cellular processes by directly phosphorylating metabolic enzymes and transcription factors. Here, we discovered a new target for GSK-3␤ phosphorylation: the human glucocorticoid receptor (GR). Glucocorticoid signaling is essential for life and regulates diverse biological functions from cell growth to metabolism to apoptosis. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 50 publications
4
102
0
Order By: Relevance
“…In fact, different phosphorylation patterns within the amino-terminal activation function-1 domain can dictate which target genes will be bound by GR (29). Both MAPKs, targets of rapid GR signaling and cyclin-dependent kinase 2 (CDK2), phosphorylate GR and influence its transcriptional activity (39). Therefore, we tested the impact of Cav-1 deletion on MAPK-and CDK2-dependent phosphorylation of GR at serine-211 (S211) and serine-226 (S226), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, different phosphorylation patterns within the amino-terminal activation function-1 domain can dictate which target genes will be bound by GR (29). Both MAPKs, targets of rapid GR signaling and cyclin-dependent kinase 2 (CDK2), phosphorylate GR and influence its transcriptional activity (39). Therefore, we tested the impact of Cav-1 deletion on MAPK-and CDK2-dependent phosphorylation of GR at serine-211 (S211) and serine-226 (S226), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…GR translocation to the nucleus also depends on a specific phosphorylation in its serine residue 232 (Galliher-Beckley et al, 2008;Wang et al, 2002) and on a physical interaction with a large chaperone protein complex consisting mainly of FK506 binding protein 51 (FKBP51) (Tatro et al, 2009). Interestingly, we found increased GR phosphorylation in Ser232 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We focused our analysis on the three phosphorylation sites within its N-terminal (Ser224, Ser232, Ser246), which regulate GR trafficking and GR-dependent gene transcription (Wang et al, 2002;Galliher-Beckley et al, 2008;Takabe et al, 2008) and that have recently been shown to be modulated by GC hormones and antidepressants in human hippocampal stem cells (Anacker et al, 2011). Specifically, we focused on the pSer224/total GR and pSer232/total GR ratios in the cytoplasm, because phosphorylation at these sites may lead to nuclear translocation of the receptor, and pSer246/total GR ratio in the nuclear compartment, because this may be important for the nuclear export of the receptor.…”
Section: Analysis Of Gr Phosphorylationmentioning
confidence: 99%
“…When FKBP5 is bound to the GR complex via HSP90, the receptor has lower affinity for its ligand and is retained in the cytoplasm; upon GC binding, GR dissociates from the chaperone complex, dimerizes, and translocates into the nucleus (Binder, 2009). GR translocation and transcriptional activity is also regulated by a complex pattern of phosphorylation on different serine residues of the receptor (Galliher-Beckley et al, 2008;Takabe et al, 2008;Wang et al, 2002). Importantly, recent work from some of the authors of the present paper (Anacker et al, 2011) has recently demonstrated that GC hormones and antidepressants indeed regulate GR function via different phosphorylation of the GR, subsequently leading to phosphorylation-dependent changes in GR-mediated gene transcription.…”
Section: Introductionmentioning
confidence: 99%